Phenotyping of Indian wheat (Triticum aestivum) genotypes for identification of rust resistance genes - and M. PRASHAR, M.S. GURJAR*, RASHMI AGGARWAL (Indian Phytopathology, 2012)
Twenty five Indian wheat genotypes were screened against diverse nine pathotypes of stem, leaf and stripe rusts for postulating rust resistance genes. Genes were postulated by infection types to different rust pathotypes for seedling resistance. Phenotyping with three pathotypes of stem rust (40-1, 40-A and 117-6) showed the presence of Sr2, Sr5, Sr7a, Sr7b, Sr9b, Sr11, Sr24 and Sr31 genes in wheat genotypes tested. The most commonly detected stem resistance genes were Sr31 and Sr2 which was present singly or in combination with other resistance genes. The presence of Sr2 (40 %) was observed in ten genotypes viz., HD 2894, HD 2687, VL 616, UP 2425, Raj 3765, HI 1531, HI 977, DBW 16, PBW 343 and WL 711(+Lr57). The stock having Sr2 gene showed resistant reaction against stem rust pathotype 40-1. The presence of Sr31 (36 %) and Lr26 (36%) was observed in nine genotypes viz. HD 2687, HD 2733, HD 2824, VL 804, UP 2425, DBW 17, PBW 343, PBW 550 and HS 240 followed by Lr13 (28%), Lr34 (24%), Lr23 (20%) and Lr24 (12%). Resistant type reaction showed the presence of Lr24 gene in HD 2888, HI 1531and HW 2004 against four pathotypes of leaf rust viz. 77-5, 77-8, 104-2, 12-1. Pathotyping data with two races of stripe rust, 46S119 and 78S84 showed presence of YrA+, Yr2, Yr 9, and Yr18 in wheat genotypes tested. Yr9 gene was observed in nine genotypes (36%), HD 2687, HD 2733, HD 2824, VL 804, UP 2425, DBW 17, PBW 343, PBW 550 and HS 240 followed by Yr2 (28%) and Yr18 (20%). This information on presence of resistance genes in wheat genotypes/cultivars will be useful for developing rust resistant genotypes in wheat breeding programs.